Penerapan Business Intelligence pada Visualisasi Data Produksi Film Horor - Geovani Haryo Saputra; Darius Andana Haris; Meirista Wulandari (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze horror film production data using a Business Intelligence approach to generate information that can support the evaluation and planning of film production processes. The data used in this study were obtained from horror treatment documents and shot lists of a feature-length horror film, containing various information related to the filming process, such as scene numbers, shot numbers, scene descriptions, involved characters, shooting locations, and cinematographic techniques employed during production. The collected data were processed and visualized using Microsoft Power BI to develop an interactive dashboard capable of presenting important information in a visual format. The dashboard was designed to provide insights into scene distribution, shot type composition, character involvement in each scene, and shooting patterns throughout the film production process. Through data visualization in the form of an interactive dashboard, directors and production teams are expected to gain a clearer understanding of the film’s visual structure and production complexity. The resulting insights can support production evaluation and facilitate more informed decision-making for future film projects.